Facility for modeling the interactions effects of neutrons fluxes with materials of nuclear reactors: main characteristics and capabilities - Shevtsov, A.B.; Bryk, V.V.; Kupriiyanova, Y.E.; Voyevodin, V.N. (Вопросы атомной науки и техники, 2015)
A triple beam ion irradiation facility has been developed to study the synergistic effects of displacement damage, helium and hydrogen on microstructure changes on structural materials under environments representative for future generation reactors. The system consists of vacuum chamber and one beam line, which allows providing simultaneously dual and triple ion irradiations. Samples can be irradiated in the wide temperature range from 350…800 0С and doses up to 1200 dpa. The ferritic-martensitic steel EP-450 was simultaneously irradiated with dual and triple beam of chromium, helium and hydrogen ions at temperature of swelling maximum 480 0C, doses 50 and 200 dpa and different levels of gases. It was shown that levels of helium and hydrogen effect on swelling parameters.